(untitled) (Journal of Atomic and Molecular Sciences, 2014)
We investigate the elastic properties and phonon dispersion of the body-centered cubic structure vanadium (V) under pressure by using the generalized gradient approximation (GGA). Our elastic constants of V at zero pressure and zero temperature are in good agreement with the available experimental data and other theoretical data. The pressure dependences of bulk modulus B and its pressure derivative B', shear modulus G, elastic Debye temperature Θ_E, elastic anisotropy factor A, Poisson ratios σ and Kleinmann parameter ζ are also presented. An analysis for the calculated elastic constants has been made to reveal the mechanical unstability of V up to 100 GPa. For the phonon dispersions of V, it is easily seen that the phonon frequencies increase as the volume decreases, the phonon mode linked to a Kohn anomaly has softened to negative values.